The author as translator. Olga Martynova`s multilingualism - Hitzke, Diana (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2018)
<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-fareast-language: EN-US; mso-ansi-language: PL; mso-bidi-language: AR-SA;">Olga Martynova writes in two languages: poetry in Russian and prose in German. Writing poetry, as Martynova states, requires very quick thinking, which is only possible for her in the Russian language. In spite of this limitation, she translates her Russian verses into German – in collaboration with Elke Erb. To consider an example, in “Verse von Rom (3)”, the Russian rhymes “инеем – именем – выменем” are rendered on the one hand literally, as “Raureif – Name – Euter”, and on the other as ‘visual rhymes’: “Namen – Kolonnaden – oben”. The paper aims to show how Martynova practises a poetics of translation. She is not afraid of coming across as a “flat” poet in translation (as for example Flaubert said about Pushkin in Turgenev’s renditions: “Il est plat, votre poète”). Instead, she writes books in German and Russian, books which are linked to each other. Another language important for her works is the language of birds. The paper analyses in what sense Martynova can be viewed as an author-translator (within a broader typology of writers).